Thyroid-Bed Schwannoma Mimicking a Thyroid Neoplasm: A Challenging Diagnosis: Report of a Case and Literature Review - Claudio Gambardella; Ludovico Docimo; Giancarlo Candela; Giovanni Cozzolino; Federico Mongardini; Francesca Serilli; Giusiana Nesta; Marcello Filograna Pignatelli; Sonia Ferrandes; Antonio Gambardella; Giovanni Docimo (Medicina, 2022)
Background: Schwannomas, also called neurinomas, are rare benign tumors of the neural cells that can develop from the sheaths of nervous structures of several districts, although the most frequent sites are the cranial nerves (25%–45%). Rarely, cases show neck schwannomas in the thyroid parenchyma, while the cases of thyroid-bed schwannomas mimicking a thyroid-gland lesions are anecdotal. Methods: We report the case of a 70-year-old man with a preoperative-imaging diagnosis of a thyroid neoplasm, confirmed as Thyr 4 by fine-needle cytology. Results: During surgery, an extra-thyroidal lesion was discovered, determined to be a neck schwannoma through definitive pathology. A literature review of cases of thyroid-bed-lesion schwannomas misinterpreted as thyroid neoplasms was carried out. Conclusions: In the case of suspicious extra-thyroidal lesions, we advocate for a close routine cooperation between the cytologist, the radiologist, and the surgeon in the attempt to reach an accurate preoperative diagnosis.